2017
DOI: 10.3389/fphys.2017.01037
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Inhibits Al-Induced Programmed Cell Death in Root Tips of Peanut (Arachis hypogaea L.) by Affecting Physiological Properties of Antioxidants Systems and Cell Wall

Abstract: It has been reported that nitric oxide (NO) is a negative regulator of aluminum (Al)-induced programmed cell death (PCD) in peanut root tips. However, the inhibiting mechanism of NO on Al-induced PCD is unclear. In order to investigate the mechanism by which NO inhibits Al-induced PCD, the effects of co-treatment Al with the exogenous NO donor or the NO-specific scavenger on peanut root tips, the physiological properties of antioxidants systems and cell wall (CW) in root tip cells of NO inhibiting Al-induced P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…1; Table 1). Indeed, exogenous NO was shown to decrease pectin levels and increase the activity of xyloglucan endotransglucosylase (important for cell expansion) in Arachis hypogaea , thus inhibiting Al adsorption to the cell wall [44].…”
Section: Discussionmentioning
confidence: 99%
“…1; Table 1). Indeed, exogenous NO was shown to decrease pectin levels and increase the activity of xyloglucan endotransglucosylase (important for cell expansion) in Arachis hypogaea , thus inhibiting Al adsorption to the cell wall [44].…”
Section: Discussionmentioning
confidence: 99%
“…These disks were placed at 26 °C in darkness for 3 days and then exposed to long-day conditions (LD; 16 h light and 8 h dark cycle). Two-functional-leaf seedlings were transplanted to a hydroponic box and cultured with 1/5 Hoagland's nutrient solution (Pan et al 2017).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…This study also indicated that H 2 S improved nutrient uptake efficiency and elevated ATPase and photosynthetic performance under Al stress (Dawood et al ). Pan et al () reported that exogenous NO alleviated Al‐induced programmed cell death in peanut root tips by inhibiting Al adsorption in cell walls, as well as lowering oxidative damage and ROS accumulation by enhancing the antioxidant defense system and reducing the peroxidation of membrane lipids. Thus, Al‐induced inhibition in root elongation was relieved by maintaining the extensibility of cell walls, decreasing pectin methylesterase (PME) activity and increasing xyloglucan endotransglucosylase (XET) activity and relative expression of the XET/hydrolase ( XTH32 ) gene.…”
Section: Functional Cross‐talk Of H2s and No Systems Under Multiple Amentioning
confidence: 99%